Effect of Citricacid on The Seedling Growth of Upland Rice (Oryza sativa L.) Varietas Situ Bagendit Under Aluminum Stress - Riza Dwiningrum; Zulkifli Zulkifli; Tundjung Tripeni Handayani (Politeknik Negeri Lampung., 2016)
The objective of this research was to know whether soaking of upland rice seed in citric acid solution could alleviate subsequent growth of seedling under aluminum stress. The experiment was conducted in plant physiologylaboratory, Department of Biology, Faculty of Mathematic and Natural Science, Lampung University on January 2016, and implemented in2 x 3 factorial designs. Factor A was aluminum with two levels: 0 mM, 5 mM and factor B was Citric Acid with three levels: 0Mm, 5Mm, 10Mm. Variables in this research were shoot length, seedling fresh weight, relative water content, and shoot root ratio. Analysis of variance was conducted at 5% significant level. If interaction factor A and B was not significant, main effect was determine with lsd test at 5% significant level, but if significant simple effect was determine with F test at 5% significant level. The result showed that interaction beetwen aluminum and citric acid decreased the shoot length 16-31%. Aluminum decreased fresh weight of seedling 11%, relative water content 3%, and shoot root ratio decreased 15%. It was concluded that soaking upland rice seed in citric acid solution was not able to alleviate subsequent growth of seedling under aluminum stress. Keyword: citric acid, aluminum, upland rice, shoot length, seedling fresh weight